Postoperative Prevention of Nosocomial Pneumonias, by Using Airway Filters under Artificial Ventilation - A. A. Yeremenko; D. Ye. Zorin; V. M. Yegorov; P. Ye. Kolpakov (Общая реаниматология)
Objective: to determine the duration of exposition of filters and their most optimum position in different types of respiratory circuits. Subjects and methods. Group 1 comprised patients receiving not more than 12-hour artificial ventilation (AV) through a coaxial respiratory-circuit, without a humidifier, moisture accumulators, and a nebulizer. The filters were set between the intubation tube and the circuit. Group 2 included patients having more than 12-hour AV through the disposal respiratory circuits including a nebulizer, a humidifier, and inspiratory and expiratory moisture accumulators. The filters were set in front of the inspiratory circuit and behind the expiratory one on an AV apparatuses. Before regularly replacing a filter and/or a circuit, samples were taken for bacteriological tests from different portions of the circuit at various intervals: 4, 12, 24, 48, 96, 120, and 144 hours after initiation of AV, as well as before tracheal extubation in a patient. Results. The data obtained during the study have indicated that the breathing circuit filters afford a reliable protection from the entry of environmental microorganisms into the patient’s respiratory tract. In Group 1, AV did not result in the occurrence of pneumonia or tracheobronchitis. The moisture accumulators and the Y-shaped connector are the most infection-susceptible parts of a respiratory circuit. Mechanical circuit contamination and a larger number of pathogenic microbial strains were observed after 4—5-day AV. Conclusion. All procedures associated with circuit seal failure should be performed, by observing the aseptic rules. The recommended time of using a respiratory circuit during prolonged AV is 96—120 hours. Key words: intensive care unit, artificial ventilation, nosocomial pneumonia, antibacterial respiratory circuit filter.